ANALISIS BUKU BAHASA ARAB KELAS VII KARYA SAEFULLAH DAN SYAEKHUDIN DITINJAU DARI ASPEK PENYAJIAN, KEBAHASAAN DAN KEGRAFIKAN - Ardiansyah; Ahmad Asrof Fitri; Hasyim Fanirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to evaluate the feasibility of the Arabic textbook “Ayo Memahami Bahasa Arab untuk MTs Kelas VII” authored by Hasan Saefulloh and A. Syaekhudin, based on three assessment aspects set by the National Education Standards Agency (BSNP): presentation, language, and graphics. This research applies a qualitative approach using a library research method and descriptive qualitative-quantitative analysis techniques. The primary data source is the analyzed textbook, while secondary data include BSNP standard documents, relevant literature, and previous research findings. The results show that the presentation aspect scored an average of 3.52 (highly feasible), the language aspect scored 3.42 (highly feasible), and the graphics aspect scored 3.40 (highly feasible). The overall average score is 3.45, placing the textbook in the “highly feasible” category for use as a learning resource for Arabic at the junior secondary level (MTs). Nevertheless, this study recommends improvements in providing a glossary, transliteration for longer texts, varied illustrations, and additional contextual sentence examples. Keywords: textbook evaluation, Arabic language, BSNP, presentation, language, graphics.